0127 Pesticide use and relative telomere length in the Agricultural Health Study. (23rd June 2014) - Andreotti, Gabriella; Hoppin, Jane; Savage, Sharon; Hou, Lifang; Baccarelli, Andrea; Hoxha, Mirjam; Koutros, Stella; Sandler, Dale; Alavanja, Michael; Beane Freeman, Laura
Abstract : Objectives: Epidemiologic studies have linked pesticide use to various health outcomes, including cancer, but underlying mechanisms remain unclear. In a previous analysis from the Agricultural Health Study (AHS), a prospective cohort study of pesticide applicators in the US, use of certain pesticides was linked to shorter relative telomere length (RTL) measured in buccal cell DNA. In this analysis we examined the associations between occupational pesticide use and RTL measured in blood DNA. Method: We conducted an analysis of 80 pesticides and RTL in 568 cancer-free male participants aged 31–94 years in the AHS. We used self-reported pesticide use information collected at study enrollment (1993–1997) and two follow-up questionnaires administered approximately 5 years apart to construct exposure metrics, including intensity-weighted lifetime days (lifetime days*intensity score). Blood samples were collected in 2006–2008, and RTL was measured in DNA using qPCR. Multivariable linear regression was used to evaluate the associations between individual pesticide use and RTL, adjusting for age at blood draw and other pesticides associated with RTL. Results: Increasing tertiles of intensity-weighted days of alachlor were associated with longer RTL (p-trend = 0.01). In contrast, increasing tertiles of intensity-weighted days of 2, 4-D (p-trend = 0.05), diazinon (p-trend = 0.01) and aldrin (p-trend = 0.01) were associated with shorter RTL. Conclusions: We found two herbicides (alachlor, 2, 4-D) and two insecticides (diazinon, aldrin) significantly associated with alterations in RTL. These pesticides have been linked to increased cancer risk in epidemiological and/or animal studies. Consistent with our finding, shorter RTL with 2, 4-D use was previously observed in an analysis of buccal cells in the AHS.